KONSEP HARTA PERSPEKTIF MAQASID AL-SYARIAH DAN IMPLEMENTASINYA PADA WAKAF TUNAI - Hidayat, Ariani (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Cash waqf is one of the instruments to empower the potential of publicfunds with the aim of alleviating poverty and other socio-economicproblems. The substance of cash waqf is in line with the maqasid alshari'atwhich leads to al-maslahah al-mursalah (universal benefit) oneof them is in order to realize social welfare through justice of incomeand wealth distribution. In addition, one of the implementation ofmaqasid al-syari'at contained in cash waqf is the principle ta'awun(mutual help) to the less fortunate.